PENCAPAIAN HASIL BELAJAR MELALUI PENUMBUHAN SIKAP MAHASISWA - Cut Aswar (UIN AR-RANIRY, 2014)
Lecturer trying to grow and improve the positive attitude of students in the study of the course so that students can learn an increased vigor in the course. Indeed, the persistence of the negative attitude of students to a course, and it does not mean all the students to be negative towards a course, otherwise many students a positive attitude towards a subject that is learned. Lecturer of the course seeks to evoke the spirit of students to love a subject and trying to build a positive attitude towards the subject that he teaches. If the student has not been able to raise it toward a positive attitude among students, it is difficult for educators to develop students are knowledgeable and skilled in mastering a subject. For students who are positive or negative attitude is always the case in the learning of a subject, and even negative attitude is more dominant than positive attitude. Thus, the learning that educators are given less attractive, so that lecturers are less able to foster a positive attitude in the students learn a subject. That the lecturer of the course is able to actualize its role optimally in the process of learning a course undoubtedly positive attitude of students in the learning will become more prevalent among students. From the description above, the attitude of a person when used in the learning activities of the course, there will be individuals who love a subject (positive attitude) or being otherwise is not like a subject (a negative attitude). For students who have a positive attitude about a course will learn of their own accord and devote full attention to the matter of the course. Instead negative student attitudes about a course would lead to inactive students in learning activities and will ultimately negative effect also on a subject that is learned